Drug utilization pattern of antidepressant used in depression disorder in psychiatric department in Northern India: a prospective observational study - Sirajo, Ibrahim; Manaal, Azha; Khan, Rukhsar; Aliyu, Aisha; Sada, Mudassir; Ajmal, M.; Badruddeen; Agrawal, Anurag (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Due to its large economic impact, severe impairment, suffering, and relatively high lifetime prevalence, depression is becoming a major health concern worldwide, its treatment involved different strategies consisting of supportive and drug therapy This work was done to evaluate the prescribing practices in treatment of depression. Methods: A prospective observational study was undertaken at the IIMS&R hospital, department of psychiatry. A total of 100 prescriptions written for patients with depressive disorders were examined along with the patients file and progress report to access the pattern of drug therapy, demographic information of patients, comorbidities, the number and types of medications given were also evaluated. Result: Among the prescriptions, 6 different class of drugs were prescribed out of which 61.26% are selective serotonin receptor inhibitors (SSRIs), 10 different individual antidepressant drugs were prescribed, escitalopram was highest 58.4% (n=83) and paroxetine 2.8% (n=4) as the least, mirtazapine 11.9% (n=17), sertraline 7% (n=10), amitriptyline 6.33% (n=9), duloxetine 6.33% (n=9), escitalopram+ clonazepam 5.6% (n=8) gabapentin+ nortriptyline 1.4% (n=2) and most of patient were within age group of 26-35 years, there is an average of 2 antidepressant drugs per prescription. Conclusions: The current study reveals important highlights on the current drug treatment pattern in the treatment of depressive disorder, including the most commonly prescribed drug, average number of drugs per prescription and the demographic distribution of patients with depressive disorder which is important for the healthcare professionals to enhance drug therapy, encourage effective healthcare delivery and improve quality in treatment of depression.